Bioresorbable scaffolds in the treatment of coronary artery disease - Zhang Y (Dove Medical Press, 2013)
Yaojun Zhang,1,2 Christos V Bourantas,1 Vasim Farooq,1 Takashi Muramatsu,1 Roberto Diletti,1 Yoshinobu Onuma,1 Hector M Garcia-Garcia,1 Patrick W Serruys11Thoraxcenter, Erasmus Medical Center, Rotterdam, The Netherlands; 2Division of Cardiovascular Diseases, Nanjing First Hospital, Nanjing Medical University, Nanjing, People's Republic of ChinaAbstract: Drug-eluting stents have reduced the risk of in-stent restenosis and have broadened the application in percutaneous coronary intervention in coronary artery disease. However, the concept of using a permanent metallic endovascular device to restore the patency of a stenotic artery has inherited pitfalls, namely the presence of a foreign body within the artery causing vascular inflammation, late complications such as restenosis and stent thrombosis, and impeding the restoration of the physiologic function of the stented segment. Bioresorbable scaffolds (BRS) were introduced to potentially overcome these limitations, as they provide temporary scaffolding and then disappear, liberating the treated vessel from its cage. Currently, several BRSs are available, undergoing evaluation either in clinical trials or in preclinical settings. The aim of this review is to present the new developments in BRS technology, describe the mechanisms involved in the resorption process, and discuss the potential future prospects of this innovative therapy.Keywords: bioresorbable scaffold, drug-eluting stent, biodegradable, design, mechanism, coronary artery disease